KONSEPSI KEBAHASAAN DALAM PANDANGAN ALIRAN LINGUISTIK LONDON - Winarsih, Suko (Jurnal Bahasa Lingua Scientia, 2012)
London School is one of the linguistic schools which creates Englsh phonetics learned by the foreigners. London School has a long history in the English linguistics. Since the eleventh century the linguists have developed the standard of English. On the sixteenth century, the experts developed practical English. They are orthoepy (language codification and the right English pronunciation teaching), lexicography, stenography, renewable English spelling and the creation of philosophy language.